Exploring Students’ Visual Thinking: Examining Students' Sequence And Series Analysis Through The Lens Of Visual Cognitive Styles - Triliana, Triliana; Ramadani, Iqbal (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2023)
Visual thinking skill has an important role in solving mathematics problems. Visual thinking not only can be applied on the topic of geometry but also on the other topics including sequence and series. The visual cognitive styles have a relationship to mathematical abilities and types of tasks. This research aims to analyze the students’ visual thinking skill viewed by visual cognitive styles on the topic of sequence and series used grounded theory approach. The steps in this study are developing visual cognitive style questionnaire and visual thinking skill test, asking students to fill the questionnaire and do the test, and analyzing the results of questionnaires and students’ answer. The subjects of this research were 2 students at the eleventh grade (16-17 year-olds). The result showed that students with spatial visualization have better visual thinking skill than object visualization. Students with spatial visualization are very good at working on problems on indicators transforming problems or concepts into visual forms. Whereas, students with object visualization are very good at drawing for the nth term of a sequence. The analysis of this research can be used as material for consideration to make the learning design on the topic of sequence and series that is in accordance with the cognitive styles of students